In vivo and in silico Evaluation of Analgesic and Hypoglycemic Activities of Roots of Acacia nilotica, Azadirachta indica and Justica adhatoda - Hussain, Fahad; Saha, Poushali; Rahman, Fahad Imtiaz; Hossain, Mohammad Salim; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2021)
The present study focuses on the investigation of methanol extracts of roots of three indigenous plants of Bangladesh namely Acacia nilotica, Azadirachta indica and Justicia adhatoda to evaluate their analgesic and hypoglycemic activities in experimental animal model along with in silico modelling of several compounds present in the root extracts of these plants. Analgesic and hypoglycemic activities were evaluated in Swiss albino mice using acetic acid-induced writhing inhibition method and glucose tolerance test, respectively. In silico molecular docking and ADME study was conducted to assess the binding affinity with the target receptors and oral bioavailability of the compounds. The methanol extracts of A. nilotica, J. adhatoda and A. indica roots at a dose of 400 mg/kg body weight reduced the number of writhes by 61.53%, 54.61% and 47.69%, respectively compared to standard diclofenac sodium (70.77% at a dose of 50 mg/kg bw) (p<0.05). A. nilotica and A. indica root extracts showed significant hypoglycemic activity at a dose of 400 mg/kg bw (% reduction of blood glucose 43.66 and 37.55% respectively, p<0.001) and J. adhatoda root extract reduced the blood glucose level by 33.71% (p<0.001) compared to that of standard drug, glibenclamide (57.46% reduction of blood glucose) after 120 minutes of administration. Among the computationally tested compounds, flavan-3-ol showed the lowest binding energy (-8.7 kcal/mol) with both COX-1 and COX-2 compared to standard diclofenac sodium (-7.8 kcal/mol). On the other hand, quercetin demonstrated the lowest binding energy (-8.8 kcal/mol) with ATP-sensitive potassium channel with Sulfonylurea Receptor 1 subunit among the tested compounds compared to standard glibenclamide (-9.3 kcal/mol). All the compounds showed high oral bioavailability in ADME analysis. Among all the root extracts, A. nilotica exhibited the most promising analgesic and hypoglycemic activities and should be employed to future investigation for isolating specific chemical constituents. Dhaka Univ. J. Pharm. Sci. 20(2): 185-197, 2021 (December)